Nurse's role in palliative care for cancer patients (Research, Society and Development, 2021)
This study discusses the importance of nurses in palliative care for cancer patients. Aims to: Highlight the importance of the role of nurses with cancer patients in palliative care. For this, the following guiding question was used: What is the importance of nurses in palliative care for cancer patients? As inclusion criteria, scientific articles were used between the years 2016 to 2021, in the databases, LILACS, BVS, SCIELO and PUBMED, in Portuguese, English, French and Spanish. As exclusion criteria, articles outside the research timeframe and which did not address the selected topic were removed. The results obtained through the 16 selected scientific articles brought about the realization of the elaboration of three thematic categories: The nurse and nursing care for patients with cancer, challenge for nurses in palliative care aimed at cancer patients and nurse management in cancer pain. The study concluded that nurses are essential in care, but face challenges in different sectors, such as deficits in professional training, work overload, frustration and difficulty in dealing with death. This professional, dealing directly with situations of suffering, in addition to every challenge in his career, can be reached because of his emotional involvement with the patient.